Second annual report of the Hospital for Natural Healing : 1936-7 - Hospital for Natural Healing (London, England) (1937)
1937 1937 1930s 13 pages useless for the troubles. In London there is a small body of people who are working with different ideas and principles, they are applying the Laws of Nature and teaching people that they are a part of this Universe and therefore are governed by the Laws governing it. These people are getting results, they are not making money, but they are helping people to return to the normal after many years of suffering and the resulting abnormality. These people, the Governors of "The Hospital for Natural Healing", claim that while most of the recognised treatments of to-day take the patient further from the normal, their treatments enable the body to work towards restoring equilibrium according to its own need. That is why they get results when others have failed. Is there a single man or woman who claims to be interested in the welfare of mankind who can afford to leave the work of "The Hospital for Natural Healing" uninvestigated? We insist that there must be a full and unbiassed investigation, and the future must depend on the results of this. 9 292/842/2/237